Digital Transactions in Business - Iffan, M; Khoir, K A (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to provide innovation and analyze transaction efficiency in traditional markets using digital technology to generate new business opportunities. This research uses library research methods, using data collection techniques by reading, recording, and processing existing data. In the digital age, traditional markets are increasingly less in demand by different groups of people, especially by the millennium for various reasons such as dirty, muddy, hot, and coupled with strong odors. The result of this research is that with the development of digital technology today, it cannot be denied that traditional markets must innovate to overcome competition. With digitalization in traditional markets, Millennial generation and various groups of people are expected to be able to transact more easily in traditional markets. This digital transaction can promote and prosper traders in traditional markets, and make traditional market traders independent in marketing their products.